VISUAL STRATEGIES IN TEACHING ENGLISH FOR STUDENTS WITH HEARING IMPAIREMENT AT SPECIAL NEEDS SCHOOL - Salsabiilah, Dhiya (Politeknik Siber Cerdika Internasional, 2024)
Deafness is a condition in which a person cannot hear well. Deaf people have a way of communicating that is different from other people's, including the way they learn things. Teaching English to students with special needs is a challenge, requiring strategies and the participation of all parties in the school environment. This study aims to describe the teacher's strategy in learning English for deaf students in Special Needs School Kota Cirebon and the challenges experienced by teachers in dealing with deaf students. This study uses qualitative techniques. Observations, interviews, and documentation were used to obtain data. The author utilizes data collection techniques, data reduction, data presentation, and drawing conclusions to analyze the collected data. According to the findings of this study, teachers use Visual Strategies in the form of visual image maps (1), introduce new knowledge with videos (2), and (3) introduce languages that were previously unknown. Preparation, student evaluation, disparities in students' innate abilities, such as communication skills, and the difficulties of learning a foreign language are the issues that teachers encounter when educating deaf kids. Despite the difficulties teachers confront, it can be said that the goal of teaching English using this method is good